"In vitro" evaluation of bacterial biofilm formation on different cerclage systems. (November 2022) - Veloso, Margarita; Lopez, Yuli; Bernaus, Martí; Gabasa, Yaiza; Angles, Francesc; Font-Vizcarra, Lluis; Soto, Sara
Cerclage wiring may be used for fracture fixation or osteotomy stabilization in revision arthroplasty. There is a lack of evidence regarding the potential risk of bacterial colonization for the different types of cerclages. The objective of our research is to study the adhesion and biofilm formation of S. epidermidis, S. aureus, and P. aeruginosa on two different cerclage cable models, comparing a polymer cable and a stainless steel metal cable. A two-cm cerclage piece of each material was submerged in 2 mL of tryptic soy broth (TSB) inoculated with 10 μL of a 0.5 McFarland bacterial culture, and incubated at 37°C during 2 h for adhesion and 48 h for biofilm formation. The cerclages were washed with 1xPBS and sonicated in a new culture medium. Aliquots of several dilutions of each sonicated culture were spread in TSB agar and incubated at 37°C for 24 h. The number of colonies was counted. The colony-forming units per ml (CFU/mL) and the percentage of reduction were calculated. Experiments were triplicated. For P. aeruginosa, a statistically significant reduction in biofilm formation was found on the polymer cerclage cable, compared to the metal cerclage cable. Reductions of 59% and 88%, after 2 h and 48 h, respectively, were observed. For S. epidermis and S. aureus, there was a trend towards lower bacterial adhesion and biofilm formation for the polymer cerclage cable. In summary, these results demonstrate that the braided polymer cerclage cable may be less prone to bacterial adherence and biofilm formation compared to the braided metal cerclage cable.